Modify Symmetric Block Cipher Algorithm Using Generated Digital 3D Fractal Image - Abdul Wahab, Hala; Sarab, Sura (Iraqi Journal of Science, 2024)
The principal goal guiding any designed encryption algorithm must be security against unauthorized attackers. Within the last decade, there has been a vast increase in the communication of digital computer data in both the private and public sectors. Much of this information has a significant value; therefore it does require the protection by design strength algorithm to cipher it. This algorithm defines the mathematical steps required to transform data into a cryptographic cipher and also to transform the cipher back to the original form. The Performance and security level is the main characteristics that differentiate one encryption algorithm from another. In this paper suggested a new technique to enhance the performance of the Data Encryption Standard (DES) algorithm by generate the key of this algorithm from random bitmaps images depending on the increasing of the randomness of the pixel colour, which lead to generate a (clipped) key has a very high randomness according to the know randomness tests and adds a new level of protection strength and more robustness against breaking methods.